DISPUTING THE NARRATIONS OF THE COMPANIONS: A Speech Acts Analysis of ‘Â’isyah RA’s Corrective Responses in Prophetic Hadîts - Ubaidillah Ubaidillah; Elvusal Mammadov (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
This article investigates ‘Â’isyah RA’s corrective interventions toward the narrations of other Companions within the corpus of Prophetic hadîts. While classical and contemporary scholarship has long acknowledged ‘Â’isyah’s role in correcting transmitted reports, existing studies have largely approached this phenomenon descriptively and have rarely examined the linguistic and pragmatic structure of her corrective discourse. Employing a qualitative pragmatic approach, this study analyzes a selected corpus of hadîts from Shahîh al-Bukhârî and Shahîh Muslim in which ‘Â’isyah RA explicitly disputes or clarifies reported narrations. The analysis draws on speech act theory as an analytical framework to identify patterns of corrective discourse, focusing on assertive, directive, and expressive acts and the linguistic markers through which they are realized, such as negation structures, evaluative verbs, and expressive formulas. Rather than treating these interventions solely as juridical or theological statements, the study interprets them as context-bound communicative acts within early hadîts transmission. The findings suggest that ‘آ’isyah’s corrective responses function as discursive mechanisms for negotiating epistemic authority at the level of narration, grounded in proximity to the Prophet and experiential knowledge. By integrating pragmatic speech act analysis with the conventions of hadîts scholarship, this study proposes a linguistic framework for examining corrective discourse in early hadîts transmission. It contributes to a more systematic understanding of how epistemic authority was negotiated within early narrational interaction.